Inside Front Cover: Observation of Robust Polarization Squeezing via the Kerr Nonlinearity in an Optical Fiber (Adv. Quantum Technol. 3/2023). Issue 3 (10th March 2023) - Kalinin, Nikolay; Dirmeier, Thomas; Sorokin, Arseny A.; Anashkina, Elena A.; Sánchez‐Soto, Luis L.; Corney, Joel F.; Leuchs, Gerd; Andrianov, Alexey V.
Abstract : The cover shows the evolution of the state of the light field represented on the Poincaré sphere (green) due to the nonlinear Kerr interaction described in article number 2200143 by Nikolay Kalinin, Gerd Leuchs, and co‐workers. The quantum uncertainty of the initial coherent two‐mode laser field is the small grey sphere on the larger Poincaré sphere which develops into the orange squeezed ellipsoid.